Accuracy of Clinical AndSonographic Estimation of Fetal Weight in The Third Trimester of Pregnancy (The Planet, 2023)
Introduction: Accurate estimation of fetal weight is most important when dealing with high-risk populations, particularly when dealing with the two extremes of birth weight. Ultrasound has been used to estimate fetal weight for over 30 years. It guides clinicians to finalize important obstetrical decisions. Aim of the study: The study aimed to assess the accuracy of clinical and sonographic estimation of fetal weight in the third trimester of pregnancy. Methods& Materials: This cross-section study was conducted at the Department of Obstetrics & Gynecology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. The study was carried out from February 2012 to July 2012. A total of 175 cases were enrolled as per inclusion criteria. Result: In this study, 7.4% patients was overweight or obese. The mean BMI was 22.67±SD.The mean symphysis-fundal height (SFH) was 35.6±1.2 cm.In the majority (86.3%) of cases,was at or above the ischial spine and 13.7% below the ischial spine.Regarding clinical and USG estimated fetal weights, and actual birth weight, (the mean) was 3109.71 gm (range: 2800-3600 gm), while the estimated birth weights by clinical and ultrasonographic surrogates were 3637.54 gm(range: 3100-4030 gm) and 3286.28 gm (range: 3000-3900 gm) respectively. Conclusion:The clinical estimation of fetal weight is one of the important and necessary skills in the management of obstetric patients because of its simplicity. But clinical estimation lies far from the approximation of the actual birth weight. Ultrasonographic estimation of the fetal weight lies nearthe actual birth weight.
Keywords: Ultrasonography; Symphysis-fundal height (SFH); Shepard Formula; Johnson Formula